2008
DOI: 10.1523/jneurosci.3545-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

The Basic Helix-Loop-Helix Transcription Factor Olig2 Is Critical for Reactive Astrocyte Proliferation after Cortical Injury

Abstract: The mechanisms underlying the formation of the glial scar after injury are poorly understood. In this report, we demonstrate that after cortical injury Olig2 is upregulated in reactive astrocytes coincident with proliferation of these cells. Short-term lineage tracing studies with glial subtype-restricted transgenic reporter lines indicate that Olig2-expressing cells in the astroglial but not the oligodendroglial lineage are the essential source of reactive astrocytes. In addition, cortical Olig2 ablation resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
90
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 28 publications
8
90
1
Order By: Relevance
“…Although transcription factors such as Stat3, c-fos, cAMP-response element-binding protein (CREB), and Olig2 are known to be required to initiate reactive gliosis in response to extrinsic factors (23)(24)(25)(26)(27)(28), Lhx2 is unique because it regulates maintenance of the nonreactive state in Müller glia. Selective loss of function of Lhx2 in Müller glia does not compromise glial survival and likewise does not affect expression of glial markers such as P27 Kip1 and Cralbp.…”
Section: Discussionmentioning
confidence: 99%
“…Although transcription factors such as Stat3, c-fos, cAMP-response element-binding protein (CREB), and Olig2 are known to be required to initiate reactive gliosis in response to extrinsic factors (23)(24)(25)(26)(27)(28), Lhx2 is unique because it regulates maintenance of the nonreactive state in Müller glia. Selective loss of function of Lhx2 in Müller glia does not compromise glial survival and likewise does not affect expression of glial markers such as P27 Kip1 and Cralbp.…”
Section: Discussionmentioning
confidence: 99%
“…Although there has been no report on the effects of Olig2 on GPC proliferation, recent studies have shown that Olig2 can regulate the proliferation of multipotent NSCs (Ligon et al, 2007). In addition, Olig2 is critically involved in the proliferation of reactive astrocytes after injury (Chen et al, 2008). Thus, it is conceivable that the activation of Olig2 can promote the proliferative capacity of multiple cell types including GPCs.…”
Section: Discussion Olig2 Overexpression Increases Cellular Proliferamentioning
confidence: 99%
“…nated lesions in mature CNS (Arnett et al, 2004). More recent studies showed the involvement of Olig2 in the differentiation of neural and/or glial progenitors after injury (Buffo et al, 2005;Chen et al, 2008). It appears that Olig1 and Olig2 have distinct biological functions that could be separable from those of each other after injury and during development (Arnett et al, 2004;Buffo et al, 2005;Xin et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Olig2 deletion in astrocytes reduces reactive astrocyte proliferation [95]. No data are currently available on injury-related signals involved in Olig2 induction in astrocytes.…”
Section: Intracellular Transduction Pathways and Cellular Reactivitymentioning
confidence: 99%